Jóvenes universitarios contemporáneos: contradicciones y desafíos - Patiño Torres, José Fernando (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2012)
The most significant results of this research allowed us to understand that there are interesting transformations in the way young people assume religion, sex, the future and university life, which shows the important role played by globalization in the formation of identities that are now more flexible, liquid and far from the moralistic logic of modernist times. It also showed that although these young people are obliged to comply with the mandate to be university students in the eyes of their family and friends, this does not mean that they know how to achieve it, nor that they have a university institution that facilitates this process. For this reason, the university, in many cases, is assumed as a "temporary escape route" that extends the social moratorium of the subjects, thus creating an illusory halo of expectation of social mobility that will probably never occur through professionalization.